An mHealth, patient engagement approach to understand and address parents' mental health and caregiving needs after prenatal diagnosis of critical congenital heart disease - Anne Chevalier McKechnie; Kristin M. Elgersma; Taylor Iwaszko Wagner; Anna Trebilcock; Jenna Damico; Alejandra Sosa; Matthew B. Ambrose; Kavisha Shah; Aura A. Sanchez Mejia; Karen F. Pridham (Elsevier, 2023)
Objective: To provide an overview of the development of the Preparing Heart and Mind™ (PHM™) care program designed for parents with a prenatal diagnosis of critical congenital heart disease (CCHD) and describe issues of parental concern, caregiving competencies, and type and timing of PHM™ topics. Methods: Guided participation theory underpinned intervention development and a mixed methods pilot of a novel, nurse-guided mHealth intervention. Parents were enrolled from the third trimester of pregnancy-12 weeks postnatally. Online surveys, session transcripts, and app use were descriptively analyzed. Results: The sample included 19 mothers/birthing persons and 15 caregiving partners randomized to the intervention group. In 49 sessions, mental health/wellbeing (94%) and condition-specific information (86%) were top issues. Many caregiving competencies were developed, with mothers/birthing persons often focused on feeding (86%). Regulating emotions and co-parenting consistently needed support. PHM™ topics of preparing for hospitalization (47%) and handling uncertainty (45%) were most discussed. Two cases further characterize findings. Conclusion: Nurse-parent collaborative understanding of issues emphasized the need for mental health assessments. Prenatal intervention opportunities were underscored through discussions of caregiving issues and PHM™ topics. Innovation: PHM™ represents an innovative approach that holds promise for supporting parents' mental health and caregiving needs outside the healthcare setting.